The INFLUENCE OF SERVICE QUALITY AND OPPORTUNISM ON PATIENT LOYALTY MEDIATED BY TRUST - Efendi; Soelasih, Yasintha; Lembana, Devi Angrahini Anni (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
The research looked at the effect of service quality and opportunism on patient loyalty mediated by trust. Sampling was done by probability sampling. The number of samples drawn is 443 from 2 hospitals in Jakarta and Karawaci, Indonesia. The results show that service quality influences customer loyalty directly and indirectly through mediating customer trust, while opportunism either directly or indirectly mediated customer trust does not affect customer loyalty. The study contributed to the theory by confirming a shorter path of service quality – trust – loyalty in healthcare service.